Joint trajectories of behavioral, affective, and cognitive engagement in elementary school. Issue 2 (4th March 2017) - Archambault, Isabelle; Dupéré, Véronique
ABSTRACT: The aim of the present study was to model student trajectories of behavioral, affective, and cognitive engagement from Grade 3 to Grade 6. The authors also examined whether teachers perceptions could predict student trajectory membership. The authors collected data from a sample of 831 students and 152 teachers. Using multiple-process growth mixture modeling, they identified 5 distinct trajectories of student engagement. Although a large majority of children presented a stable and high level of engagement on the three dimensions over time, more than one third of them showed a lower or changing level of engagement as the years progressed. These students were more likely to be boys and to be perceived by teachers as being less engaged. They also present more learning or behavioral problems and share less positive relationships with teachers. The results support the need to consider group-based differences when designing and adapting prevention and intervention strategies to favor student engagement.